Estland: Eine ordnungspolitische Erfolgsgeschichte? - Jüri Sepp (OrdnungsPolitisches Portal (OPO), 2007)
Estonia with its foundations of economic system belongs amongst favorites of liberal economists. Foreign economical openness, stable money through the currency board arrangement exchange rate system, simple tax system with proportional income tax rate, rapid and transparent privatization for real money have guaranteed one of the world fastest economic growth so far. At the same time, the real level of Estonian economic development is one of the lowest in Europe regardless of transition period during last 15 years and EU integration. The GDP per capita, even taking into account purchasing-power parity, stays in the fifth decimal in world at the latest data. Nevertheless, international indicators of development potential, which are under the observation in this article, refer to further convergence opportunities for Estonia with developed countries. Summary figures of competitiveness, which synthesize all development assumptions, give for Estonia the position in the third decimal. Even better is the situation from the aspect of economic indexes, which stress on institutional factors. Here Estonia has a position in borderline of first ten. Only exception here is the labor market regulation. In general the institutional environment of Estonian economy may consider for promoting as competitiveness as well economic growth initially. However, present development factors have limited scope of impact in resource and effectiveness based development level. Innovation based stage development presumptions are not formed by current time.
Keywords: 330; Estonia; transformation; institutional environment; competitiveness